2002
DOI: 10.1021/ja025869r
|View full text |Cite
|
Sign up to set email alerts
|

Built to Order:  Molecular Tinkertoys from the [Re6(μ3-Se)8]2+ Clusters

Abstract: Ligand substitution of [Re(6)(mu(3)-Se)(8)(PEt(3))(5)(CH(3)CN)](SbF(6))(2) (1) with pyridyl-based ligands, 2,4,6-tri-4-pyridyl-1,3,5-triazine (L1) and 5,10,15,20-tetra(4-pyridyl)-21H,23H-porphine (L2), produced respectively the star-shaped tricluster (T1) and tetracluster (T2) arrays, wherein three (T1) and four (T2) units of the [Re(6)(mu(3)-Se)(8)](2+) core-containing clusters are interconnected by the corresponding bridging ligands. These novel supramolecular assemblies were characterized by a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 16 publications
0
32
1
Order By: Relevance
“…The dominate, common synthetic approach to such solids is through metal salt coordination to reactive groups on the capping ligands of the superatoms (for examples, see DiSalvo, Long, Fedorov, and Zheng). Superatoms with rhenium are particularly prominent in these examples, as their chemistry has been richly developed: site‐differentiated [Re 6 Se 8 ] superatoms have been synthesized and extensively studied, as well as their assembly into oligomers, supramolecular arrays, and dendrimers . These assemblies, while structurally interesting, do not exhibit significant inter‐superatom interactions.…”
Section: Materials From Superatomsmentioning
confidence: 99%
“…The dominate, common synthetic approach to such solids is through metal salt coordination to reactive groups on the capping ligands of the superatoms (for examples, see DiSalvo, Long, Fedorov, and Zheng). Superatoms with rhenium are particularly prominent in these examples, as their chemistry has been richly developed: site‐differentiated [Re 6 Se 8 ] superatoms have been synthesized and extensively studied, as well as their assembly into oligomers, supramolecular arrays, and dendrimers . These assemblies, while structurally interesting, do not exhibit significant inter‐superatom interactions.…”
Section: Materials From Superatomsmentioning
confidence: 99%
“…The facility of encapsulating biologically relevant clusters into dendrimers has further been illustrated by Aida et al [31], who prepared dendrimer encapsulated copper(µ-oxo)dimers (found in methane monooxygenase and ribonucleotide reductase) and Basu et al who prepared dendrimer encapsulated oxo-Mo(V)tetrasulfide units (found in DMSO reductase) [32]. Significant contributions have also come from Kaifer et al [33][34][35][36][37][38] who have reported dendrimers based on ferrocenyl and viologen core moieties and Zheng et al, who have reported dendrimers based on a Re 6 Se 8 cluster core moiety [39][40][41].…”
Section: Synthesis Of Metal Cluster Core Dendrimersmentioning
confidence: 99%
“…Structural transformationst riggered by solvent, including for SCAMs, are interesting and useful, [8a,b] which could produce novel structures and have potential applications in molecular switches, sensors, data storage, and display devices. [7c, 9] Relativelys ubtle electronic modifications to the linker can induced iffering structures, [10] although there are as yet no reportede xamples of their influences in single-crystal to single-crystals tructural transformations. In addition,t he geometrical structure and electronic properties of the SCC are easily affected and transformed in solvents.…”
Section: Introductionmentioning
confidence: 99%